AKTIVITAS ANTIDIABETES DARIEKSTRAK ETANOL BIJI HANJELI (Coix lacryma-jobi) PADAMENCITGALUR SWISS WEBSTER YANG DIINDUKSI ALOKSAN - Elis Susilawati (Universitas Bhakti Kencana, 2015)
Diabetes mellitus is a disease which is marked by increasing glucose blood levels because of absolut or relative insulin deficiency. Hanjeli seeds (Coix lacryma Jobi) was expected to have an antidiabetic activites. This study aimed to determine the antidiabetic activity of ethanol extract of hanjeli seeds (Coix lacryma Jobi). This study was conducted by in – vivo, in which the male Swiss Webster mice was induced by alloxan intravenously with dose 50-55 mg/Kg. The 30 mice were randomly divided into six groups, the positive control group, negative control group, the dose I group (100 mg/kg bw), the dose II group (200 mg / kg bw), dose III group (400 mg/Kg bw), and the glibenclamide 0,65 mg/kg bw group. The data were analyzed using One Way Anova and Post-hoc LSD test. The results showed that there were no significant difference in the decreasing of glucose blood level between hanjeli seed etanol extract doses of 100 mg/kg bw, 200 mg/Kg bw, and 400 mg/Kg bw compared to the positive control. In conclusion, the ethanol extract of hanjeli seeds can not decrease glucose blood levels. Keywords: Kata kunci: